På felttur i fortiden. Etnografien bag bogen om folkloristen Evald Tang Kristensens fodtur blandt folk på heden 1873 - Christiansen, Palle Ove (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
NB: Artiklen er på dansk, kun resuméet er på engelsk. The article deals with the interdisciplinary, methodological background to the book, De forsvundne. Hedens sidste fortællere [The Disappeared. The Last Storytellers From The Moors], by Palle Ove Christiansen and Else Marie Kofod (2011). The publication integrates work methods from folklore, history and anthropology. The point of departure is a presentation of selected ballads and folk tales recorded by the world’s greatest folklorist, Evald Tang Kristensen (1843-1929). Rather then publish the material in the form of literary genres or the informants’ personal repertoire, the authors chose to present it in the way it was collected “in the field” on one of Tang Kristensen’s walking tours on the heaths of Jutland in 1873. This perspective draws much more attention to the modern, full-time fieldwork in the 1870s in which Kristensen was a pioneer in Denmark. The account of this fieldwork required micro-historical reconstruction of Kristensen’s route (through heathland that has now disappeared), the informants’ domiciles and living conditions. In order to fill in the gaps in our archival knowledge, it was necessary to trace various historical circumstances in the localities where the 1873 expedition’s informants lived. The authors thus ended up carrying out a form of historical fieldwork themselves. The article illustrates the advantages to the project of combining work methods from various disciplines. Three selected cases are used to describe some of the problems that the authors encountered in carrying out their historical fieldwork in the former heathland and human traces left on them.